Mean Platelet Volume and Its Relation With Arterial Stiffness in Patients With Normotensive Polycystic Kidney Disease. (1st March 2013) - Orscelik, Ozcan; Kocyigit, Ismail; Akpek, Mahmut; Dogdu, Orhan; Kaya, Coskun; Unal, Aydin; Sipahioglu, Murat; Tokgoz, Bulent; Zengin, Halit; Oymak, Oktay; Kaya, Mehmet Gungor
Abstract : Background: Autosomal-dominant polycystic kidney disease (ADPKD) demonstrates cardiovascular manifestations, such as hypertension, myocardial infarction, and increased carotid intimae-media thickness. These complications are the main cause of morbidity and mortality in patients with ADPKD. Platelet activation and arterial stiffness are important manifestations that independently predict cardiovascular events. In the present study, we aimed to investigate the relation between arterial stiffness, mean platelet volume (MPV), and highly sensitive C-reactive protein (hs-CRP) in patients with normotensive polycystic kidney disease. Methods: We included 30 normotensive subjects with ADPKD with an estimated glomerular filtration rate (eGFR) of 60 mL or more per minute per 1.73 m 2, 30 normotensive subjects with ADPKD with eGFR from 30 to 60 mL/min per 1.73 m 2, and 30 healthy controls in our study. Pulse wave velocity (PWV), eGFR, spot urine protein-creatinine ratio, MPV, and hs-CRP levels were measured in all participants. In addition, transthoracic echocardiography and ambulatory blood pressure monitoring were performed. Results: Age, sex, biochemical markers, eGFR, hemoglobin level, and platelet count were similar in the ADPKD subjects and the controls. There were significant differences in MPV (9.8 ± 0.7, 8.7 ± 0.8, and 8.0 ± 0.5 femtolitre; P < 0.001) and hs-CRP (6.8 ± 3.0, 5.3 ± 2.7, and 2.6 ± 0.52 mg/L; P < 0.001) in the groups. Additionally, PWV values were increased from healthy subjects to ADPKD patients who have decreased eGFR (5.5 ± 1.1, 8.8 ± 1.6, and 10.8 ± 1.2 m/s; P for trend <0.001). There were significant positive correlations between PWV and MPV ( r = 0.401; P = 0.002) and hs-CRP ( r = 0.343; P = 0.007) in the patients with ADPKD. Additionally, PWV was independently predicted by MPV (β = 0.286; P = 0.007), proteinuria (β = 0.255; P = 0.001), eGFR (β = −0.479; P < 0.001), and hs-CRP (β = 0.379; P < 0.001) in the patients with ADPKD. In addition, eGFR, as a sign of severity of disease, was independently predicted by MPV (β = −0.325; P = 0.003), PWV (β = −0.471; P < 0.001), and hs-CRP (β = −0.269; P = 0.008). Conclusions: Our findings suggest that MPV and hs-CRP levels are associated with increased arterial stiffness in patients with early-stage ADPKD and those with late-stage ADPKD. Also, MPV and hs-CRP were independently associated with the severity of ADPKD.